Representation and taxation in the American South, 1820-1910 - Jensen, Jeffrey L.; Pardelli, Giuliana; Timmons, Jeffrey F. (Cambridge : Cambridge University Press, 2023)
We explain and document state-level fiscal developments in American Southern states from 1820-1910, focusing on their main source of revenue, progressive property taxes borne primarily by economic elites. The fourteen states in our analysis were characterized by severe economic exploitation of the enslaved and later politically repressed African-descended population by a small rural elite, who dominated the region both politically and economically. While rural elites are thought to be especially resistant to taxation, we offer a set of conditions that explains the emergence of progressive taxation and provides a coherent account of the fiscal development of these states over this period. Using an original, archival data set of annual tax revenues and select expenditure items, we show that the economic interests of these rural elites and the extent of their formal (over)representation played a critical role in shaping the observed fiscal patterns within and across these states over this period. This title is also available as Open Access on Cambridge Core.
Title from publisher's bibliographic system (viewed on 25 Dec 2023).
Keywords: Property tax -- Southern States -- History -- 19th century; Elite (Social sciences) Southern States History -- 19th century